Legal Protection for Consumers Against the Presence of Hazardous Chemical Substance Sodium Dehydroacetate in Food Products - Dini, Arinda Prima; Caesar Purwanto, Aldira Mara Ditta (Jurnal Meta-Yuridis, 2025)
This research aims to examine the legal protection and liability provided to consumers against the presence of hazardous chemical substances in food products. This study employs a normative legal research method with a prescriptive approach to formulate recommendations for addressing the identified legal issues. It utilizes both statutory and conceptual approaches. The research findings indicate that legal protection consists of two types: preventive and repressive. Preventive legal protection is carried out by the National Agency of Drug and Food Control (BPOM) as a government institution responsible for food safety supervision. Meanwhile, repressive legal protection grants consumers the right to file claims when they suffer losses, either through litigation or non-litigation mechanisms. Keywords: Legal Protection, Consumers, Sodium Dehydroacetate.